Kikuchi-Fujimoto disease: A rare case of pyrexia of unknown origin - Sadatia, Vishal; Thakker, Mayank; Ambaliya, Devang (Indian Journal of Case Reports, 2024)
A young male was referred to a clinician for a complaint of fever of short duration with non-specific joint pain and treated for 1 week but after some time again presented with the same complaints with severe epigastric tenderness and vomiting. There was no past medical history before this episode. When cervical lymph node biopsy was performed gave us the diagnosis of histiocytic necrotizing lymphadenitis (Kikuchi-Fujimoto disease). A rare form of necrotizing lymphadenitis is an uncommon, benign, self-limiting disorder of obscure etiology. It affects mostly young adults of both genders. Clinically, it presents with fever and lymphadenopathy of a firm to rubbery consistency frequently involving cervical lymph nodes while weight loss, splenomegaly, and leukopenia in severely ill patients.